Freedom and Equality : the Moral Basis of Democratic Socialism - Dixon, Keith (Routledge revivals., 2009)
Unashamedly polemical, this reissue of Freedom & Equality, first published in 1986, presents a strong and persuasively argued case for democratic socialism. In contrast to many recent books justifying conservatism and varieties of Marxism, Keith Dixon defends the two great principles underpinning democratic socialism freedom and equality. He aims both to restore the idea of freedom to its proper place in the political vocabulary of the left and to defend a stark version of freedom as absence of constraint. Only this version of freedom, he argues, is consistent with the proper defence of civ.